From carrier dynamics inside fused silica to control of multiphoton-avalanche ionization for laser machining - Lei, Shuting; Grojo, D.; Barillot, T.; Gertsvolf, M.; Chang, Zenghu; Rayner, D. M.; Corkum, P. B. (Institute of Electrical and Electronics Engineers, 2010)
Using pump-probe measurements, we characterize carrier decay time inside fused silica and measure deeply bound self-trapped excitons. With pump-probe delay, we also control free carrier injection and the subsequent avalanche process for laser machining applications.
Keywords: Multiphoton processes; Ultrafast processes; Condensed matter; Semiconductors